Estimating neoplasia detection rate (NDR) in patients with Barrett's oesophagus based on index endoscopy: a systematic review and meta-analysis. Issue 12 (14th March 2019) - Parasa, Sravanthi; Desai, Madhav; Vittal, Anusha; Chandrasekar, Viveksandeep T; Pervez, Asad; Kennedy, Kevin F; Gupta, Neil; Shaheen, Nicholas J; Sharma, Prateek
Abstract : Background: Biopsies are obtained to confirm intestinal metaplasia and rule out prevalent dysplasia and cancer when Barrett's oesophagus (BE) is detected at index upper endoscopy (oesophagogastroduodenoscopy [EGD]). Aim: The purpose of this systematic review was to obtain summary estimates of the prevalence of high-grade dysplasia (HGD) and oesophageal adenocarcinoma (EAC) associated with BE during index EGD for chronic GERD symptoms, defined as neoplasia detection rate (NDR) which could be used as a quality measure. Methods: An extensive search was performed within PUBMED, EMBASE and the Cochrane Library databases to identify studies in which patients underwent index endoscopy for the evaluation of the presence of BE. Two reviewers independently evaluated both the study eligibility and methodological quality and data extraction. A random-effects model (REM) based on the binomial distribution was used to calculate the pooled effects of the prevalence of BE-associated dysplasia and EAC. Results: For the calculation of dysplasia and EAC prevalence rates, a total of 11 studies with 10 632 patients met the inclusion criteria including 80.4% men with a mean age of 58.7 years and average BE length of 3.5 cm. The pooled prevalence of EAC, HGD and LGD was 3%(95% CI 2 to 5, 9 studies: 396/10 539 patients), 3%(95% CI 2 to 5 [REM], 9 studies: 388/10 539 patients) and 10%(95% CI 7 to 15 [REM], 10 studies: 907/8945 patients), respectively. For NDR, that is, the pooled prevalence of HGD/EAC was 7%(95% CI 4 to 10 [REM], 10 studies: 795/10 632 patients). Conclusion: NDR is approximately 4% and could be used as a quality measure.